Analyzing the Lyrics of 'How Do I Live': A Study on Textual and Contextual Perspectives - Patty, Jusak; Que, Stella Rose (MATAI: International Journal of Language Education, 2023)
This discourse analysis focuses on the emotional narrative of Diane Warren's song "How Do I Live?" employing a comprehensive framework encompassing textual and contextual dimensions. The study scrutinizes the grammatical and lexical aspects, unveiling intricate linguistic devices used to convey sentiments of love and longing. The analysis highlights the song's linguistic richness and emotional depth through meticulous examination of reference, ellipsis, conjunction, repetition, synonymy, and collocation. Additionally, a contextual interpretation sheds light on the personal, locational, and temporal dimensions, emphasizing the immediacy and urgency of the writer's emotional experience. Personal deixis, featuring first and second-person pronouns and the endearing address "baby," creates a powerful emotional connection between the writer and the loved one. Spatial deixis employs metaphors to vividly depict the writer's emotional world, emphasizing the profound impact of the loved one on their emotional well-being. Temporal deixis, featuring a mix of tenses and time-related expressions, grounds the emotional narrative in relatable moments of longing and apprehension. This analysis showcases how the song effectively combines linguistic and contextual elements to create a poignant narrative, providing valuable insights into the complex interplay of language, emotions, and narrative in song lyrics.